Impact of Legal Systems on Women's Representation in Parliament: Egypt and Tunisia - Rabie, Omar (AUC Knowledge Fountain, 2024)
This thesis explores the disparities in women's representation in the parliaments of Egypt and Tunisia, underscoring the impact of legal systems on political participation. Through a comparative analysis, it identifies key differences and similarities in the legal frameworks of both countries, highlighting how this influences the level of women's parliamentary representation. Egypt, with its relatively low representation of women in Parliament, contrasts with Tunisia's significantly higher levels attributed to progressive legal reforms and quota systems. The research employs a mixed-method approach, combining qualitative and quantitative data to explore the institutional, legal, and cultural factors affecting women's political empowerment. By examining the historical context, electoral laws, and constitutional provisions, this study contributes to understanding the complexities surrounding women's political participation in the Arab world. It offers insights into the legal and social barriers to women's representation and proposes recommendations for enhancing gender parity in political institutions.